Cerebrospinal fluid biogenic amines depletion and brain atrophy in adult patients with phenylketonuria. Issue 3 (1st February 2019) - Pilotto, Andrea; Blau, Nenad; Leks, Edytha; Schulte, Claudia; Deuschl, Christian; Zipser, Carl; Piel, David; Freisinger, Peter; Gramer, Gwendolyn; Kölker, Stefan; Haas, Dorothea; Burgard, Peter; et al.
Abstract: Biogenic amines synthesis in phenylketonuria (PKU) patients with high phenylalanine (Phe) concentration is thought to be impaired due to inhibition of tyrosine and tryptophan hydroxylases and competition with amino acids at the blood‐brain barrier. Dopamine and serotonin deficits might explain brain damage and progressive neuropsychiatric impairment in adult PKU patients. Ten early treated adult PKU patients (mean age 38.2 years) and 15 age‐matched controls entered the study. Plasma and cerebrospinal fluid (CSF) Phe, 5‐hydroxyindoleacetic acid (5‐HIAA), 5‐hydroxytryptophan (5‐HTP), 3, 4‐dihydroxy‐l ‐phenylalanine (l ‐DOPA) and homovanillic acid (HVA) were analyzed. Voxel‐based morphometry statistical nonparametric mapping was used to test the age‐corrected correlation between gray matter atrophy and CSF biogenic amines levels. 5‐HIAA and 5‐HTP were significantly reduced in PKU patients compared to controls. Significant negative correlations were found between CSF 5‐HIAA, HVA, and 5‐HTP and Phe levels. A decrease in 5‐HIAA and 5‐HTP concentrations correlated with precuneus and frontal atrophy, respectively. Lower HVA levels correlated with occipital atrophy. Biogenic amines deficits correlate with specific brain atrophy patterns in adult PKU patients, in line with serotonin and dopamine projections. These findings may support a more rigorous Phe control in adult PKU to prevent neurotransmitter depletion and accelerated brain damage due to aging.